Victorian labour history : experience, identity and the politics of representation - Host, John, 1946- (Routledge, 1998)
Orthodox historical accounts of popular experience in mid-Victorian Britain suggest certain homogenous and seemingly clear stable social and political orders. Host re-examines the historical debate and challenges conventional interpretations.